2020
DOI: 10.3390/pathogens9110869
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the MIE Locus During HCMV Latency and Reactivation

Abstract: Human cytomegalovirus (HCMV) is a ubiquitous herpesviral pathogen that results in life-long infection. HCMV maintains a latent or quiescent infection in hematopoietic cells, which is broadly defined by transcriptional silencing and the absence of de novo virion production. However, upon cell differentiation coupled with immune dysfunction, the virus can reactivate, which leads to lytic replication in a variety of cell and tissue types. One of the mechanisms controlling the balance between latency and reactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 285 publications
(382 reference statements)
0
45
0
Order By: Relevance
“…Brie y, after the virus envelope fuses with the plasma membrane of the host cell, the enveloped virus particles are released into the cytoplasm, enter the nucleus through the nuclear pore within a few minutes and release viral DNA triggering the different phases of gene expression. Dooley et al [17] reported that after HCMV infection, through the combined action of chromatin remodeling and transcription factors, the genes expressed in the MIE phase play an important regulatory role in the balance between latent infection and lytic infection. This molecular switch involves the action of a large number of host and viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Brie y, after the virus envelope fuses with the plasma membrane of the host cell, the enveloped virus particles are released into the cytoplasm, enter the nucleus through the nuclear pore within a few minutes and release viral DNA triggering the different phases of gene expression. Dooley et al [17] reported that after HCMV infection, through the combined action of chromatin remodeling and transcription factors, the genes expressed in the MIE phase play an important regulatory role in the balance between latent infection and lytic infection. This molecular switch involves the action of a large number of host and viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is also not known whether different sites of myeloid latency (e.g., CD34+ progenitor cells and their derivative CD14+ monocytes) have different latency-associated gene expression signatures. Crucially, in both cell types, the major immediate early promoter/enhancer (MIEP) remains suppressed during latency [ 78 , 79 ]. During latency, viral DNA replication does not occur, and many viral antigens are not expressed.…”
Section: Strategies For Targeting the Latent Hcmv Reservoirmentioning
confidence: 99%
“…A combination of viral and cellular factors are known to act to modulate the transcriptional activity of the MIE locus [ 94 , 95 , 96 ], for reviews see [ 79 , 97 , 98 ]. One such cellular factor is the histone deacetylase HDAC4, which is upregulated in latently infected cells and associates with the MIEP, deacetylating histones to aid in its repression [ 99 ].…”
Section: Strategies For Targeting the Latent Hcmv Reservoirmentioning
confidence: 99%
“…HCMV is a human beta-herpesvirus that causes lifelong infection in the host and has been involved in the development of several diseases in humans, generating severe complications in immunocompromised individuals [ 64 , 65 ]. At various micromolar concentrations, the anti-HCMV activity of curcumin was explored in vitro, in an animal model (Balb/c mice) and in silico experiments.…”
Section: Role Of Curcumin In Inhibition Of Various Herpesviruses Imentioning
confidence: 99%